Study on the Effects of Multiple Matings in Coccinella transversalis for its Behaviour and Reproduction (Journal of Institute of Science and Technology, 2019)
The evolution and maintenance of multiple mating (repeated mating or polyandry) in predaceous ladybird beetles (Coleoptera: Coccinellidae) is an adaptive puzzle; since a single ejaculate of male often provides enough sperm to female for her lifetime egg production. Despite numerous studies on multiple mating evaluating reproductive attributes, there are negligible studies that investigated changes in behavioural patterns in ladybirds during multiple mating. In the present study, effects of multiple mating on mating behavioural pattern of males and reproductive attributes of females have been assessed using Coccinella transversalis as an experimental ladybird species. Results revealed that during copulation behaviour, time for the commencement of mating, latent period, wriggling movement duration, number of bouts and mating duration decreased with increase in number of mating; whereas interval between successive bouts increased significantly. Moreover, fecundity and egg viability of females increased with increase in number of mating.